2021
DOI: 10.1038/s41598-021-89745-9
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell adaptation to pregnancy requires prolactin action on both beta and non-beta cells

Abstract: Pancreatic islets adapt to insulin resistance of pregnancy by up regulating β-cell mass and increasing insulin secretion. Previously, using a transgenic mouse with global, heterozygous deletion of prolactin receptor (Prlr+/−), we found Prlr signaling is important for this adaptation. However, since Prlr is expressed in tissues outside of islets as well as within islets and prolactin signaling affects β-cell development, to understand β-cell-specific effect of prolactin signaling in pregnancy, we generated a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…Identification of the site of action is an important step to determining the mechanism of prolactin receptor activity, and if this will be a useful target for intervention. Our work has replicated previous studies that have deleted Prlr specifically from the beta-cells (11), pancreas (12), and adult onset deletion from the pancreas (42) demonstrating that Prlr activity in the pancreas is required for maternal adaptations in beta-cells during pregnancy. Moreover, in the current study we have demonstrated that these transgenic mice lines with beta-cellor pancreas-specific deletions of the Prlr also show deletion of Prlr in the hypothalamus, particularly the arcuate nucleus, an area known to contribute to central regulation of insulin secretion and glucose homeostasis (18-20, 35, 43, 44).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Identification of the site of action is an important step to determining the mechanism of prolactin receptor activity, and if this will be a useful target for intervention. Our work has replicated previous studies that have deleted Prlr specifically from the beta-cells (11), pancreas (12), and adult onset deletion from the pancreas (42) demonstrating that Prlr activity in the pancreas is required for maternal adaptations in beta-cells during pregnancy. Moreover, in the current study we have demonstrated that these transgenic mice lines with beta-cellor pancreas-specific deletions of the Prlr also show deletion of Prlr in the hypothalamus, particularly the arcuate nucleus, an area known to contribute to central regulation of insulin secretion and glucose homeostasis (18-20, 35, 43, 44).…”
Section: Discussionsupporting
confidence: 87%
“…A critical omission from previous studies examining the effect of specific deletion of Prlr from the pancreas ( 11 , 12 ) was an examination of the brain to determine the extent to which central Prlr were affected in these transgenic mice lines ( 15 ). This has been somewhat addressed in a recent study in mice in which Prlr was deleted from the pancreas in adulthood using a tamoxifen-inducible Cre line, as mRNA for Prlr in the entire hypothalamus was reported to be no different to control mice ( 42 ). Given that we only detected recombination of the Prlr gene in a small population of cells in the arcuate nucleus using the Pdx-cre line, however, and that Prlr is extensively expressed in the hypothalamus ( 16 ) it is perhaps not surprising that no change of Prlr mRNA would be detected when assessing the entire hypothalamus as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GDM, inactivation of prolactin receptors on the surface of islet β cells promotes apoptosis and inhibits proliferation of β cells ( Banerjee et al, 2016 ). Moreover, down-regulation of prolactin action in non-beta cells during pregnancy negatively secondary affects beta cell gene expression and increases beta cell susceptibility to external injury ( Shrivastava et al, 2021 ). Adiponectin plays an important role in the proliferation of beta cells during pregnancy by promoting prolactin expression in trophoblast cells ( Qiao et al, 2021 ).…”
Section: Pathophysiological Features Of Gdmmentioning
confidence: 99%
“…While the models of PRL overexpression and PRLR activation have been informative, their conclusions are confounded by multiple factors in the endogenous pregnancy milieu [ 8 , 12 , 13 , 14 , 15 ]. Litter size dictates exposure to PL expression during pregnancy, making it difficult to titrate PL concentrations in vivo to understand how PL activates PLR signaling.…”
Section: Introductionmentioning
confidence: 99%